Implementasi Metode Axiomatic Design pada Perancangan Cooling Box untuk Distribusi Pengiriman Es Puter - Permana, Muhammad Priya; Samodro, Guntur (Universitas Muhammadiyah Sorong, 2026)
Every region in Indonesia has its own unique way of celebrating events, whether happy or sad, in the form of celebrations. Celebrations are also a means of introducing culinary treasures that are closely linked to the culture and local wisdom of a region. These culinary treasures are accompanied by the growth of the catering business. The main focus of the culinary aspect is ice cream. The challenge lies in the distribution and delivery from the production site to the event location to maintain the temperature and keep it cold. This study designed a cooling box using the Axiomatic Design method. Axiomatic Design is a design method in which decision-making and perspectives are based on consumer desires. Therefore, this study focuses on describing and translating consumer needs into abstractions in the form of design functions, which are then linked to parameters. Data collection was conducted using open questionnaires and interviews with ice cream entrepreneurs. The results of the study focused on 1) the design of handles on the cooling box located on the sides for lifting into vehicles; 2) the design of cooling box locks to keep the lid tight and easy to open; 3) the design of the coating on the walls of the cooling box to maintain the temperature of the ice cream. The validity test results showed a p-value greater than 0.05 (p > 0.05), indicating that there was no difference between the proposed design and the needs of ice cream entrepreneurs.